A Roman shipwreck with a cargo of Apuan marble (marmor lunense) at Punta del Francese (Stintino‐Sassari, Sardinia). (13th July 2020) - Beltrame, C.; Lazzarini, L.; Antonelli, F.
Abstract : The wreck‐site of Punta del Francese (Stintino‐Sassari) off the island of Sardinia (Italy) is composed of 14 roughly cubic blocks and slabs of marble lying in an almost coherent arrangement. Archaeometric analyses indicate a provenance of the entire cargo of marble from the Apuan Alps ( marmor lunense ) of north Italy. Fragments of amphoras confirm its dating to the Flavian period (first century ce ). The dimensions of the cargo, and especially of the single blocks, suggest it would have been destined for the building of an important public monument in western Hispania or southern Gallia. A first hypothesis for the ship's sailing route, and a comparison with the other cargoes of marble from Luna, are proposed.